Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/eji.201041354
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cells in systemic lupus erythematosus: The long and short of it all

Abstract: Plasma cells can be classified as long-or short-lived. The lifespan of a plasma cell largely depends on whether it arises from a germinal center or an extrafollicular locus and most importantly whether it can find a survival niche in the spleen or BM. In systemic lupus erythematosus (SLE) patients, long-lived plasma cells are believed to be responsible for the production of anti-RNA and anti-cardiolipin antibodies, whereas short-lived plasma cells, which are more susceptible to anti-proliferation therapies, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
(48 reference statements)
3
29
0
Order By: Relevance
“…In addition, it was reported that expanded PCs, which were generated through GCs in both the peripheral and bone marrow in SLE patients, 45,46 are responsible for the production of an array of autoantibodies against soluble and cellular constituents that are most commonly nuclear antigens. 47 Consistent with previous reports, the expression of CCND3 is significantly higher in GC B cells than in non-GC B cells, 7,8 and the expression of miR-15b in IMQ-treated GC B cells is significantly lower than IMQ-treated and wild-type non-GC B cells. The different expression levels and functions of CCND3 in different B-cell subsets indicated that CCND3 plays different roles in different stages and contexts, and that even the same type of cells may express different level of genes under different circumstances.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it was reported that expanded PCs, which were generated through GCs in both the peripheral and bone marrow in SLE patients, 45,46 are responsible for the production of an array of autoantibodies against soluble and cellular constituents that are most commonly nuclear antigens. 47 Consistent with previous reports, the expression of CCND3 is significantly higher in GC B cells than in non-GC B cells, 7,8 and the expression of miR-15b in IMQ-treated GC B cells is significantly lower than IMQ-treated and wild-type non-GC B cells. The different expression levels and functions of CCND3 in different B-cell subsets indicated that CCND3 plays different roles in different stages and contexts, and that even the same type of cells may express different level of genes under different circumstances.…”
Section: Discussionsupporting
confidence: 91%
“…The anti-BAFF Ab belimumab reduces anti-dsDNA, anti-Smith, anticardiolipin, and anti-ribosomal P autoantibodies, normalizes C3/C4 complement levels, and decreases the amount of naive and activated B cells and PCs, but it does not deplete memory B cells (57). As such, the fraction of anti-dsDNA Abs secreted by short-lived PCs (SLPCs) (58), whose numbers correlate with flares (12), is targeted by belimumab whereas the Ab titers against pneumococci, tetanus, and influenza representing LLPCs are not reduced (59). This underscores the necessity to block both compensating BCMA ligands, that is, APRIL and BAFF, to deplete LLPCs (8,60).…”
Section: Autoreactive Pcsmentioning
confidence: 99%
“…Both mechanisms are central to the pathogenesis of SLE. Plasma cells produce much of the autoantigen specific antinuclear antibodies (ANAs) that are responsible for several pathological manifestations associated with SLE (e.g., glomerulonephritis, cardiomyopathies, dermatitis) [21]. Activation of the NF-ÎșB cascade leads to several proinflammatory cytokine cascades that perpetuates the proliferation and differentiation of autoantigen specific T and B cells and drives the initial innate immune response that potentiates lupus-like symptoms in the early in disease [22].…”
Section: Introductionmentioning
confidence: 99%